2014
DOI: 10.1080/03650340.2014.936855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grain yield indices in hexaploid wheat genotypes in response to drought stress

Abstract: Drought stress limits crop production in the world. Therefore, employing high-yielding cultivars tolerant to drought is an effective approach to reduce its detrimental effects. To identify drought tolerant genotypes, 36 wheat genotypes were evaluated during the 2010-2011 and 2011-2012 growth seasons. A field experiment was conducted in a split plot design with two irrigation treatments (100% field capacity until harvest and no irrigation after anthesis) as main plots in three replications and genotypes as subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 19 publications
8
23
0
Order By: Relevance
“…Warrington et al (1977) explained that drought stress at anthesis may lead to yield loss by reducing TKW and if accompanied with high temperatures after anthesis, accelerates whole plant senescence and reduces biological yield and HI. Bayoumi et al (2008) and Dorostkar et al (2015) observed that grain yield, biological yield, HI and TKW decreased under stress condition.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Warrington et al (1977) explained that drought stress at anthesis may lead to yield loss by reducing TKW and if accompanied with high temperatures after anthesis, accelerates whole plant senescence and reduces biological yield and HI. Bayoumi et al (2008) and Dorostkar et al (2015) observed that grain yield, biological yield, HI and TKW decreased under stress condition.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Grain number and single grain weight are reduced under drought stress or waterlogging stress in grain filling stage (de San Celedonio et al, 2014;Zhang et al, 2014), which results in significant reduction in yield (Dorostkar et al, 2015). Irrigation can increase the duration of grain filling by prolonging the functional period of leaves, which can in turn increase grain weight (Verma et al, 2004).…”
Section: Grain Yield and Wuementioning
confidence: 99%
“…Researchers have highlighted the importance of changes in cultivars rank in multi environments trials as evident from literature (Dorostkara et al, 2015). Non parametric measures were based on ranks and stable genotypes possess relatively constant rank across environments (Asghar et al, 2008;Delić et al, 2009).…”
Section: Introductionmentioning
confidence: 99%